Psychosocial Evaluation of Prospective Living Kidney Donors in Qatar: A Profile of Prospective Donors, Process, and Outcomes - Riadh A. S. Fadhil, MD; Asma Al Abdulghani, MBBS, MS; Majid Alabdulla, MD, ABPsych; Nighat A. Ajmal, MD, ABPsych; Nicoleta R. Stanciu, BSN; Sabera I. Baqi, BSN; Pratibha Ratheesh, PhD; Dominique E. Martin, PhD (Transplantation Direct)
Background. In Qatar, the Committee for Oversight of Living Donation (COLD) was established at Hamad Medical Corporation in 2014 to provide standardized, multidisciplinary psychosocial evaluation (PE) for prospective living kidney donors (PLKDs) and ensure appropriate care throughout evaluation, donation, and postdonation follow-up, consistent with legal and ethical standards. We describe the COLD protocol and report PE outcomes of PLKDs in Qatar. Methods. A retrospective observational cross-sectional study was conducted using case file data of PLKDs assessed at Hamad Medical Corporation between August 2014 and December 2022. Descriptive statistics analyzed demographics and outcomes of COLD evaluation. Results. Eight hundred ninety-eight PLKDs (54% men) were enlisted for 545 transplant candidates. Four hundred forty-seven PLKDs (49.8%) were Qatari; the remainder were noncitizen residents representing 43 nationalities. Most 680 PLKDs (76%) claimed a genetic relationship with recipients; 20% were emotionally related and 4.34% were unrelated. Of those who proceeded with evaluation, 88% (n = 788) were accepted, 7.5% were declined, and 4.8% dropped out. Of those who were declined (n = 67), 81% were noncitizen residents; 42% claimed an emotional relationship with the intended recipient, whereas 34% were unrelated and 24% were genetically related. The main reasons for declining a PLKD were insufficient socioeconomic support, psychological unfitness, and coercion by employers or family. Conclusions. Standardized structured PE has been effective in identifying and addressing risk factors across various PLKD demographics in Qatar. This study highlights the importance of comprehensive evaluation for all PLKDs, regardless of nationality or relationships with recipients. The COLD protocol could serve as a valuable tool for PE of PLKDs in other countries.